2013
DOI: 10.3109/15360288.2013.847889
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Analytical Approaches for Urine Drug Testing to Evaluate Medication Adherence in Chronic Pain Management

Abstract: This comprehensive review of analytical methods used for urine drug testing for the support of pain management describes the methods, their strengths and limitations, and types of analyses used in clinical laboratories today. Specific applications to analysis of opioid levels are addressed. Qualitative versus quantitative testing, immunoassays, chromatographic methods, and spectrometry are discussed. The importance of proper urine sample collection and processing is addressed. Analytical explanations for unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…Thus, nonconfirmed immunoassay results can misinform clinicians and even cause a risk when drug-testing results are used during judicial decisions. Note that the issues discussed here for ADHD medicines are very similar to the controversy over urine drug testing in pain management monitoring (McMillin et al 2013;Reisfield et al 2007b).…”
Section: Confirmatory Analysismentioning
confidence: 92%
“…Thus, nonconfirmed immunoassay results can misinform clinicians and even cause a risk when drug-testing results are used during judicial decisions. Note that the issues discussed here for ADHD medicines are very similar to the controversy over urine drug testing in pain management monitoring (McMillin et al 2013;Reisfield et al 2007b).…”
Section: Confirmatory Analysismentioning
confidence: 92%
“…In addition to the need for identifying and monitoring unfamiliar yet critical quality aspects of a clinical MS test such as ion suppression, 12 sample preparation techniques are often significantly more complex than routine clinical testing. 13 Furthermore, the expertise needed to troubleshoot assay performance issues must span a complex workflow that includes numerous steps in the sample preparation, chromatographic separation (if included), and detection by the various forms of MS that may be used.…”
Section: Approaches To Drug Testingmentioning
confidence: 99%
“…More detailed reviews on the principles of MS can be found elsewhere. 13,20 Since LC-MS/MS does not use antibodies for detection, there is no concern for cross-reactivity with other compounds, and therefore it is not susceptible to the falsepositive results commonly encountered with immunoassays. Disadvantages of LC-MS/MS include decreased accessibility and increased expense.…”
Section: Principles Of Ms Testing: Lc-ms/msmentioning
confidence: 99%
“…However, its long-term clinical use can be complicated by misuse, abuse, and aberrant behaviors [1, 2]. Urine drug test (UDT) has been used to evaluate the compliance of opioid therapy and detect illicit drug use in chronic pain management [39]. In a clinical study of nearly one million urine samples, a large number of patients appeared to be non-compliant with their prescribed pain medications.…”
Section: Introductionmentioning
confidence: 99%